Grid-connected control of PV-Wind hybrid energy system - Hakim Azoug; Hocine Belmili; Fekkak Bouazza (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
ABSTRACT Article history: Received Oct 14, 2020 Revised Mar 22, 2021 Accepted Apr 23, 2021 This paper presented a strategy for modeling, simulation and control of a hybrid grid connected power system which is in fact a rather complex system. In this work, we study how to use two renewable energies in an efficient manner without any disturbing of the main network. Our hybrid energy system (HES) is composed by two renewable energy sources, the photovoltaic source and wind source. It is better for these two systems to work at their maximum power in order to return the investment cost of the system. The proposed solution is to connect those generators to the electrical grid via the AC bus with trackers. Where the photovoltaic generator (PVG) is followed by a DC/DC boost converter, controlled by a perturb and observe (P&O) tracker, then followed by a three-phase voltage inverter (3-ph-VSI) which is controlled by the watt-var decoupled method. The wind system is based on permanent magnet synchronous machine (PMSM) which is used as a variable speed generator and directly connected to the turbine (without gearbox) followed by back-to-back converters. The grid side converter (GSC) allows us to control the DC bus voltage and unity power factor, while the machine side converter (MSC) ensures us to control the PMSM speed. Knowing that pitch angle control is not considered in our study. The MPPT control strategy, which is based on the optimum peak speed ratio (OTSR), is used to ensure the most energy efficiency despite variations in wind speed. The coupling of the two systems is done via the Point of Common Collecting (PCC). Finally, simulation results show the feasibility of our solution and the good performances of the proposed control strategy, applied for mediumsized HES in power generation. They also demonstrate that such system topology is very advantageous.